Making implausible futures possible: The challenges of cultural psychology. (September 2019) - Pérez Huenteo, Camila Alejandra
This article is a review of the book "The challenges of cultural psychology. Historical legacies and future responsibilities", edited by Gordana Jovanović, Lars Allolio-Näcke and CarlRatner (2019) and published by Routledge. In this book, several authors cover both origins and current developments of cultural psychology, contributing to a biographical perspective of this science. Regarding the theoretical proposals of cultural psychology, besides reviewing them thoroughly, this work encourages a reflection on how these proposals could improve people's lives. This work evinces the colonization of the natural science model over cultural psychology. In other words, it describes how mainstream psychology has been forced to adopt natural science's methods as their own, even though their objects of study are deeply different. Likewise, this book declares how the natural science model has shaped servility, favoring a political and economic system that in turn, favors only elites. In this sense, cultural psychology has one major challenge ahead: to form an alliance with those excluded groups, with whom it shares the experience of resistance. Probably, it is difficult to visualize a future where this exclusion does not exist. However, to imagine those futures that seem implausible, it is the first step to make them possible.